2011
DOI: 10.1002/mds.23460
|View full text |Cite
|
Sign up to set email alerts
|

Validation of screening instruments for neuroepidemiological surveys of tic disorders

Abstract: The efficiency of different screening instruments for tic disorders seems to vary in different settings. Telephone-based interviews may be a valid and convenient backup to ascertain the diagnosis of tic disorders when face-to-face neurological examination is not possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 18 publications
0
26
0
2
Order By: Relevance
“…In previous validation studies, A‐TAC has shown good test–retest measures, excellent inter‐rater reliability, and construct validity 48, 49, 50, as well as convergent validity with the Child Behaviour Check List 51. ADHD traits were calculated as the sum of scores of both the inattention and hyperactivity–impulsivity scales, yielding between 0 and 19 points.…”
Section: Methodsmentioning
confidence: 99%
“…In previous validation studies, A‐TAC has shown good test–retest measures, excellent inter‐rater reliability, and construct validity 48, 49, 50, as well as convergent validity with the Child Behaviour Check List 51. ADHD traits were calculated as the sum of scores of both the inattention and hyperactivity–impulsivity scales, yielding between 0 and 19 points.…”
Section: Methodsmentioning
confidence: 99%
“…Each participating child underwent a basic assessment that included demographic data (age, gender), a standardized tic screen [9] , and two spiral drawings. Thus, each participant was asked to draw two spirals, as described previously [10] .…”
Section: Study Assessmentmentioning
confidence: 99%
“…There have been no surveys of the prevalence of mild action tremor in children. A cross-sectional study of tics and other neurological disorders was conducted in Spanish children [9] , and we used this opportunity to study tremor in more than 800 randomly selected schoolchildren in the community of Burgos, Spain. Each child drew spirals with each hand, and tremor was systematically quantified using a clinical rating scale.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous reliability analysis for 37 teenagers with TD [9], the intra-rater reliability of the telephone-based interview vs. in-person neurological interview for TD has shown a kappa coefficient of 0.83. A historical diagnosis of TD was made if all essential criteria of tics were fulfilled, including the presence of repetitive movements or vocalizations, preceded by urge and followed by relief, fluctuating in severity and variety over time, not due to medicine/drug administration or any medical condition [9]. If some of the essential criteria were not fulfilled, a diagnosis of possible TD was established.…”
Section: Methodsmentioning
confidence: 99%
“…It was a cross-sectional study of a cohort of 1,867 mainstream schoolchildren (mean age 10.9 ± 2.9 years; 53.9% males). The methodology has been extensively described elsewhere [8,9] (online suppl. file).…”
Section: Methodsmentioning
confidence: 99%